1999
DOI: 10.1080/00049539908255344
|View full text |Cite
|
Sign up to set email alerts
|

The comparative psychology of marsupials

Abstract: Outdated views on behavioural evolution held that marsupials should be less "smart" than standard laboratory mammals. Changing attitudes, based on ecological, physiological, and phylogenetic considerations, led to the conclusion that marsupial mammals represent an alternative rather than an inferior mammalian design. We review the available research on marsupial psychology and conclude that the most studied marsupial, the American opossum, may be one of the most successful nonhuman animals ever tested on many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…Marsupial species were traditionally incorporated into studies of learning so that the performance of eutherian mammals could be compared with that of a group presumed to be evolutionarily less "complex" (for a review, see Wynne & McLean, 1999). Phylogenetic analyses have now revealed that marsupial mammals diverged from placental mammals about 100 million years ago and represent a parallel evolutionary lineage (Springer, Westerman, & Kirsch, 1994).…”
Section: Marsupial Mammalsmentioning
confidence: 99%
“…Marsupial species were traditionally incorporated into studies of learning so that the performance of eutherian mammals could be compared with that of a group presumed to be evolutionarily less "complex" (for a review, see Wynne & McLean, 1999). Phylogenetic analyses have now revealed that marsupial mammals diverged from placental mammals about 100 million years ago and represent a parallel evolutionary lineage (Springer, Westerman, & Kirsch, 1994).…”
Section: Marsupial Mammalsmentioning
confidence: 99%
“…Such a program would need to take cultural evolution into account, which may have been far more important than genetic evolution in the emergence of human cognition (Laland & Brown 2002). Increasing costs and a greatly increased regulatory burden have led to a reduction in the range of species studied by psychologists in recent decades (Wynne & McLean 1999). Given that evolutionary considerations are of limited value when it comes to understanding the mechanisms of cognition, we believe a systematic program of reinvigorated comparative psychology is essential to understand the uniqueness of the human condition.…”
Section: A C K N O W L E D G M E N T Preparation Of This Commentary Wmentioning
confidence: 99%
“…In New Zealand they threaten the native bird population by decimating the forests and eating birds eggs, and they spread TB to cattle. Understanding the sensorium of pest animals such as possums is useful in developing strategies to control them (Brockie, Fitzgerald, Green, Morris, & Pearson, 1984; Clout & Sarre, 1997; Wynne & McLean, 1999), but very little is known about possums' senses. For instance, only four studies concerned with their sense of hearing have been published (Aitkin, Gates, & Kenyon, 1979; Gates & Aitkin, 1982; Signal, Foster, & Temple, 2001; Winter, 1976).…”
mentioning
confidence: 99%